ANALISIS POSTUR KERJA DAN KELELAHAN OPERATOR STORE MATERIAL MIXING PT TRIPLUS HITECH BATAM - Heryansyah, Gilang; Prakasa Hasibuan, Rizki (Computer Science and Industrial Engineering, 2022)
There are a number of activities that are carried out manually and encourage an individual to have competence in the muscles and bones. However, the competence possessed by an individual is very limited so that when carrying out activities manually, it is not uncommon for complaints to occur in the muscles, namely Musculoskeletal Disorders (MSDs). the activitiy at PT Triplus Hitech are still manual, especially in the process before and after mixing the resin material, therefore there are a number of complaints on this activity. The purpose of this analysis is to see the subjective complaints of MSDs, the ergonomics risk ratio and the relationship between age, work posture, body mass index, smoking behavior in MSDs complaints. The media used is NBM questionnaires, pictures of work postures and questionnaires on worker characteristics. in the NBM questionnaire, the subjective complaint most felt was in the waist with a value of 40 (100%). in this analysis using the REBA method with calculations carried out to obtain high risk level data, namely in groups before the resin material mixing process an average of 11 and in the section after the resin material mixing process The average is 9.3. According to the results of analysis tests related to a number of complaints on MSDs including age, body posture and body mass ratio, it has a significance value of <0.05, and that which is not related to MSDs complaints, namely smoking has a significance value of > 0.05.